Optimalisasi Peran Modal Intelektual Terhadap Kinerja Karyawan - H Helmiatin (ETIKONOMI, 2015)
Optimalization of Intelectual Capital to Employee's PerformanceThe aim of this study is to obtain information on the role of intellectual capital on employee performance at Indonesia Open University. Structural Equation Model (SEM) with PLS were used to analyzed data. Result showed that human capital does not affect the performance of employees significantly, while customer capital and structural capital significantly influence employee performance. Performance can be measured by various methods, intellectual capital is not to measure the intrinsic factor of human performance, but rather to look at the preference of the operational activities of human resources in the organization and to increase the value of the organization, which in turn satisfy StakeholdersDOI: 10.15408/etk.v14i1.2263